An iliac artery aneurysm - Leksa, Natalia; Leksa, Dawid; Gałuszka, Łukasz; Uryniak, Adam; Aebisher, David; Galiniak, Sabina; Bartusik-Aebisher, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Isolated common iliac artery aneurysms (CIAs) are rare. The rarer are rupture of the common iliac artery. We can treat them surgically: classic or endovascular. Open surgery has a main role in the management of aneurysms not suitable for repair by endovascular techniques. Aim. The aim of the study is to present the possibility of occurrence of such a disease at a young age, to indicate non-characteristic symptoms that may predict the above-mentioned disease entity at the level of a primary care physician or SOR. Review of medical publications from 2000-2019 regarding guidelines or methods of conduct in that cases. Description of the case. A patient 39 years old, admitted to the Department of Vascular Surgery, in an interview: about 15 years ago severely beaten, as a result of injuries total loss of hearing, memory and basic skills such as: speech, writing, reading, hospitalized over 6 months. Conclusion. Good rehabilitation and patient persistence restored cognitive skills. Advances in surgical has lowered the mortality and morbidity rates even in patients.
Keywords: arteriography; iliac artery aneurysms; intravascular therapy; Stent-Graft